Chemical composition of endemic Stachys subnuda Montbret & Aucher ex Benth. essential oil and its anti-inflammatory and antioxidant activities - DOĞAN, AHMET; ŞEN, ALİ; BİTİŞ, LEYLA (TAYLOR & FRANCIS INC, 2019)
The essential oil of aerial parts of Stachys subnuda Montbret & Aucher ex Benth (S. subnuda) was analyzed by gas chromatography (GC) and GC/mass spectrometry (MS). Anti-inflammatory activity was evaluated by lipoxygenase inhibition assay. The antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azinobis-3-ethylbenzothiozoline-6-sulfonic acid (ABTS) assays. Sixty-two constituents, comprising 97.1% of the total essential oil composition, were identified. Phytol (25.2%), beta-caryophyllene (11.2%), germacrene D (6.9%), and hexadecanoic acid (6.9%) were the major compounds of aerial part essential oils of S. subnuda. The essential oil showed significant radical scavenging activity with 50% inhibition (IC50) values of 0.124 and 0.204 mg/mL for ABTS and DPPH radicals, respectively. The essential oil exhibited moderate anti-inflammatory activity with an IC50 value of 0.419 mg/mL. The results indicated that S. subnuda essential oil had good anti-inflammatory and antioxidant activity. Also, this is first study on chemical composition, anti-inflammatory and antioxidant activity of S. subnuda essential oil.
Keywords: Stachys subnuda; essential oil; anti-inflammatory activity; antioxidant activity; VOLATILE CONSTITUENTS; BETA-CARYOPHYLLENE; PHYTOCHEMICAL ANALYSIS; BIOLOGICAL-ACTIVITIES; ANTICANCER ACTIVITY; DIFFERENT REGIONS; CENTRAL APENNINES; RECH. FIL.; L.; LAMIACEAE